Dynamical Properties of HIV/AIDS Model with Saturated Treatment - Beay, Lazarus Kalvein; Ilwaru, Venn Yan Ishak; Ansori, Muhammad Fandi; Bakarbessy, Lusye; Dahoklory, Monce; Saija, Maryone (Jambura Journal of Biomathematics (JJBM), 2025)
Mathematical models are crucial for developing control strategies,  understanding disease transmission dynamics, and solving real-world problems. In this study, it applied a novel approach to the HIV/AIDS model. The saturated treatment was essentially used to model HIV/AIDS. A significant analysis of the HIV/AIDS epidemic model was presented, incorporating the new parameter. The mathematical analysis conducted on the model involved the examination of its boundedness,  determination of its equilibria, calculation of the HIV/AIDS reproductive number, and assessment of the stability of these equilibria.  The verification of the convergence analysis confirmed the effectiveness of the proposed scheme. The numerical results and simulations of the HIV/AIDS model are shown.  Biologically, we have conducted investigations to determine the effect of several parameters on the dynamics of HIV/AIDS transmission.